2004
DOI: 10.22358/jafs/73749/2004
|View full text |Cite
|
Sign up to set email alerts
|

A study of rumen fill on eating behaviour and voluntary intake in sheep using rumen digesta exchange method

Abstract: In order to test the infl uence of rumen fi ll on eating behaviour and voluntary intake in sheep offered hay, the rumen digesta from sheep at two hours after feeding was exchanged with that from sheep immediately before feeding. Four rumen-cannulated sheep were fed with grass hay ad libitum. Two pairs were made consisting of one sheep in the group fed at 8.30 and another sheep in the 10.30 group. The rumen digesta of the two sheep within a pair were exchanged at 10.30. We analysed the relationship between eati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The measures selected were: Body condition score (BCS) [14,20,21,22], rumen fill [23,24], fleece cleanliness [10], fleece condition [10], skin lesions [10], tail length [25,26], dag score [16], foot-wall integrity [27,28,29], hoof overgrowth [27,28,29] and lameness [10]. They were considered valid on the basis that they have been shown to have validity in previous studies, further details are reported in Munoz et al [19].…”
Section: Methodsmentioning
confidence: 99%
“…The measures selected were: Body condition score (BCS) [14,20,21,22], rumen fill [23,24], fleece cleanliness [10], fleece condition [10], skin lesions [10], tail length [25,26], dag score [16], foot-wall integrity [27,28,29], hoof overgrowth [27,28,29] and lameness [10]. They were considered valid on the basis that they have been shown to have validity in previous studies, further details are reported in Munoz et al [19].…”
Section: Methodsmentioning
confidence: 99%